A Descriptive Study On Reading Teaching-Learning Process At The Seventh Grade Of SMP N 2 Sawit Boyolali In 2013/2014 Academic Year - Rulianto, Dwi, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This study focuses on reading teaching-learning process at the seventh grade of SMP N 2 Sawit Boyolali. This study is aimed at describing the teaching objective, curriculum, syllabus, material, aspect of the process of reading, classroom procedure in reading teaching-learning process, classroom activities in reading teaching-learning process, the roles of teacher, method for teaching reading, the roles of students, and problem faced in reading teaching-learning process. This is descriptive one especially ethnography research. The subject of the study is the seventh grade students of SMP N 2 Sawit Boyolali which consists of 24 students. The writer uses non-statistical analysis to analyze the data. Based on the research finding, the objective of teaching in SMP N 2 Sawit Boyolali is to enrich the students' vocabulary by providing the material to memorize. Besides, the students understand the text both the content of the text and the tittle of the text when the teacher is explaining the material. And the students recognize the instruction when the teacher asked the students to transtale the sentence. The curriculum is the 2006 Curriculum. The syllabus is based on school level-based curriculum. The material used in reading teaching-learning process were only the Workbook. The methods used by the teacher in teaching-learning process of reading in SMP N 2 Sawit is Genre-based Approach (GBA). The English teacher applies two approaches, namely: bottom-up and top-down. The procedures of reading teaching-learning process involve in four main procedures, namely Building Knowledge of Field (BKOF), Modeling of the Text (MOT), Joint Construction of the Text (JCOT), and Individual Construction of the Text (ICOT). There are five aspects to the process of reading: phonics, phonemic awareness, vocabulary, reading comprehension, and fluency. The teacher's roles are as a monitor, controller, and model. The students' roles are as listener and performer. The writer also finds problems faced by the teacher are the teacher finds difficulties in managing the students in the class, the students did not focus in learning English, and the low input value of the students and problem faced by the students are the students have low motivation in learning English, the students have problem in interpreting the content of English reading, the students also have difficulties in translating the words from English into Indonesian and Indonesian into English, and the students have bad pronunciation. is in writing a word or sentence.